Environmental Law. - Chynoweth, Paul (International Journal of Law in the Built Environment: Volume 6, Issue 1/2., 2014)
In this Environmental Law special issue there are two-part papers from the UK on the subjects of the role of private nuisance in environmental protection and the contaminated land regime, along with a paper examining trends in 'green leases' in England and Wales and a theoretical perspective on modern day planning law. From the other side of the globe there are contributions from two Australian academics, which consider different aspects of biodiversity conservation. There is also a fascinating case study on the impact of the Commonwealth Games in Delhi on the River Yamuna and a paper from the.